Title VII and African American Hair: A Clash of Cultures - Taylor Mioko Dewberry (Washington University Journal of Law & Policy, 2017)
This Note discusses the possible motivations behind grooming policies across various industries that disproportionally disfavor African-Americans from adopting natural hairstyles. Dewberry frames the analysis in light of current protections under Title VII case law and other factors of implicit bias. The author suggests that Title VII fails to recognize hair discrimination as racial discrimination, and the importance of hairstyles as a racial identifier. The Note proposes a shift from using Title VII litigation to including minority voices in shaping grooming policies in an effort to incorporate objective criteria instead of subjective standards that leave room for implicit bias.
Keywords: Race; Grooming Policies; Natural Hairstyles; Title VII; Discrimination; Racial Identifier; Bias